Coastal landscape pattern optimization based on the spatial distribution heterogeneity of ecological risk - Yi, Lin; Ma, Sunjie; Tao, Shiwei; Zhang, Jiyi; Wang, Jiujuan (Frontiers in Marine Science, 2022)
The increasingly intensified development of coastal cities causes excessive consumption of natural resources, leading to environmental damage and increasing conflict between development and ecologial protection. In addition to emphasizing ecological development, planners should pay more attention to the practical optimization and regulation of the developed landscape pattern. Taking Dafeng as an example, this study constructs a landscape-pattern optimization method suitable for the spatial distribution heterogeneity of ecological risk-level units in the coastal zone. The study is based on (a) an analysis of the composition and evolution characteristics of Dafeng’s coastal landscape elements, (b) the landscape pattern index of the ecosystem’s overall risk assessment, and (c) the minimal cumulative resistance (MCR) model. The study uses an ecosystem service value to build a resistance model by analyzing the medium and high-risk composition and distribution characteristics of space unit elements. Finally, 26 ecological sources, 14 ecological nodes, and 17 ecological corridors (total length 169.63 km) were built. The optimized coastal zone landscape pattern jointly protects the landscape area of high ecological value by 462.02 km2. The total ecological value is 105,01.71 million yuan. Landscape connectivity has been optimized, as well as the ecosystem’s stability and total service value. The optimization method proposed in this paper can reduce the protection area and cost. The spatial optimization unit is highly targeted, providing new ideas for the coastal cities to implement their ecological development and protection strategies.